Agent Based Individual Trafficguidance - Wansher, Jørgen Bundgaard (Proceedings from the Annual Transport Conference at Aalborg University, 2020)
When working with traffic planning or guidance it is common practice to view the vehicles as a combined mass. From this models are employed to specify the vehicle supply and demand for each region. As the models are complex and the calculations are equally demanding the regions and the detail of the road network is aggregated. As a result the calculations reveal only what the mass of vehicles are doing and not what a single vehicle is doing. This is the crucial difference to ABIT (Agent Based Individual Trafficguidance). ABIT is based on the fact that information on the destination of each vehicle can be obtained through cellular phone tracking or GPS systems. This information can then be used to provide individual traffic guidance as opposed to the mass information systems of today – dynamic roadsigns and trafficradio. The goal is to achieve better usage of road and time. The main topic of the paper is the possibilities of using ABIT when disruptions occur (accidents, congestion, and roadwork). The discussion will be based on realistic case studies.